Efficiency of High-Flow Nasal Cannula on Pulmonary Rehabilitation in COPD Patients: A Meta-Analysis. (5th October 2020) - Fu, Cuiping; Liu, Xin; Zhu, Qingqing; Wu, Xu; Hao, Shengyu; Xie, Liang; Li, Shanqun
Abstract : Introduction . The clinical benefit of high-flow nasal cannula (HFNC) on factors related to pulmonary rehabilitation in chronic obstructive pulmonary disease (COPD) patients remains unclear. This meta-analysis aimed at synthesizing the available evidence on the efficacy of HFNC on exercise capacity, lung function, and other factors related to pulmonary rehabilitation in COPD patients. Methods . Electronic databases (MEDLINE, Embase, Cochrane Central Register of Controlled Trials, Web of Science) were searched for randomized trials comparing with conventional oxygen therapy (COT) or noninvasive ventilation (NIV). Primary outcomes were respiratory rate, FEV1, tidal volume, oxygen partial pressure, total score of St. George's respiratory questionnaire, 6-minute walk test, and exercise endurance time. Results . Ten trials met the criteria for inclusion. Combined data from six studies showed that HFNC showed a lower respiratory rate in COPD patients [mean difference -1.27 (95% CI: -1.65–(-0.89)]. Combined data from three studies showed a lower forced expiratory volume in one second (FEV1) in the group of HFNC. No difference in tidal volume was showed between the HFNC and control groups in COPD patients. No significant oxygen improvement between the HFNC groups and control groups. The total score of St. George's respiratory questionnaire was improved by the subgroup analysis of HFNC versus COT but no NIV. Two multicenter RCTs showed the six-minute walk test, and statistical results showed that the length of the six-minute walk capacity was increased after usage of HFNC compared to the control group [mean difference -8.65 (95% CI: -9.12–(-8.19)]. No increase of exercise capacity after usage of HFNC (mean difference -12.65). Conclusion . In the first meta-analysis of the area, the current evidence did not show so much positive effect on tidal volume or oxygen improvement in COPD patients. Length of the six-minute walk capacity was increased after using HFNC, while other pulmonary rehabilitation parameters, namely, the score of St. George's respiratory questionnaire and exercise capacity show no increase in the group of HFNC. The variance in the quality of the evidence included in this meta-analysis highlights the need for this evidence to be followed up with further high-quality and more randomized trials.